2019
DOI: 10.3390/ani9070422
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Ratio of Insoluble Fiber to Soluble Fiber in Gestation Diets on Sow Performance and Offspring Intestinal Development

Abstract: To investigate the effects of the ratio of insoluble fiber to soluble fiber (ISF:SF) on sow performance and piglet intestinal development, we randomly assigned 64 gilts to four treatments comprising diets with the same level of dietary fiber, but different ISF:SF values of 3.89 (T1), 5.59 (T2), 9.12 (T3), and 12.81 (T4). At birth and weaning, six piglets per treatment at each phase were slaughtered for sampling. As ISF:SF increased, the mean piglet body weight (BW) at weaning and piglet BW gain, which were all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
2
19
1
Order By: Relevance
“…The villus height to crypt depth ratio is a useful criterion for estimating the likely digestive or absorptive capacity of the small intestine [25]. Li et al reported an increased crypt depth of the jejunum in weaned piglets with an increased maternal insoluble fiber/soluble fiber ratio [26]. Similarly, in the present study, the villi/crypt ratio of duodenum and jejunum were significantly higher in piglets around four weeks.…”
Section: Discussionsupporting
confidence: 70%
“…The villus height to crypt depth ratio is a useful criterion for estimating the likely digestive or absorptive capacity of the small intestine [25]. Li et al reported an increased crypt depth of the jejunum in weaned piglets with an increased maternal insoluble fiber/soluble fiber ratio [26]. Similarly, in the present study, the villi/crypt ratio of duodenum and jejunum were significantly higher in piglets around four weeks.…”
Section: Discussionsupporting
confidence: 70%
“…Some studies have shown that dietary fiber supplementation not only promotes satiety in sows but also improves sow feed intake during lactation ( 28 , 30 , 31 ); however, the effects of dietary fiber supplementation from different sources are inconsistent and may be closely related to the physicochemical properties and fermentability of dietary fiber ( 20 , 27 , 28 , 32 , 33 ). Here, we found that the addition of different fiber sources to the diet of sows in mid and late gestation affected the performance of both sows and piglets, with AM in particular significantly reducing the IUGR rate, increasing feed intake during lactation, and improving sow and piglet performance.…”
Section: Discussionmentioning
confidence: 99%
“…Continued oxidative stress leads to chronic inflammation [48] and detrimentally affects growth performance [49]. Our previous study showed increased average daily gain of piglets during lactation when the ISF/SF ratios in the pregnancy diet were 3.89 and 5.59 [50]. Therefore, the dietary fiber composition in the maternal pregnancy diet has an important effect on the health of mothers and offspring, and there is a threshold ratio of insoluble to soluble fiber to ensure that the dietary fiber is effective.…”
Section: Discussionmentioning
confidence: 99%